A Pre-Experimental Study To Assess The Effectiveness Of Self-Instructional Module On Knowledge Regarding The First Aid During Convulsion Among Primary School Teachers Of Selected Schools At Metropolitan City - Kamble, Sonal Satish (Journal of Neonatal Surgery, 2025)
First aid is the assistance given to any person suffering a sudden illness or injury with care provided to preserve life, prevent the condition from worsening, and promote recovery. It includes initial intervention in a serious condition prior to professional medical help being available, such as performing cardio-pulmonary resuscitation while awaiting an ambulance as well as the complete treatment of minor conditions, such as applying a plaster to a cut. A convulsion is a medical condition where body muscles contract and relax rapidly and repeatedly, resulting in uncontrolled actions of the body. The term convulsion is sometimes used as a synonym for seizure. An abnormal electrical activity in the brain is seizure or convulsion which gives rise to is a paroxysmal, time-limited change in motor activity and behaviour, sensory disturbance or autonomic dysfunction.